Ancestry of photic and mechanic sensation? - Fritzsch, Bernd; Wittbrodt, Joachim; Arendt, Detlev (Science, 2005)
In their report “Ciliary photoreceptors with a vertebrate-type opsin in an invertebrate brain” (29 Oct. 2004, p. 869), D. Arendt et al. offer an interesting perspective on the ancestry of vertebrate and invertebrate opsins and their associated receptors. Here, we offer an even broader